2021
DOI: 10.1002/ijgo.13942
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic safety of laparoscopic surgery for women with apparent early‐stage uterine serous carcinoma: A multi‐institutional retrospective cohort study

Abstract: Cancer of the endometrium is the most common malignancy of the female reproductive system in developed countries, its incidence and associated mortality are increasing because rates of obesity have risen. [1][2][3] Two broad histologic types of endometrial cancer were proposed by Bokhman in 1983. 4 Type I tumors, affecting about 80% of cases, are mediated primarily by hyperestrogenism and are generally associated with a good prognosis. 2,5 Type II endometrial cancers, in contrast, have no exact pathogenesis. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…So far, some retrospectively designed studies about the oncological safety of minimally invasive surgery for type II EC have been published. Including 295 patients from four Chinese teaching hospitals, the study conducted by Xu et al found that for apparent early-stage uterine serous carcinoma, the approach of surgical staging was not an independent prognostic factor for oncological outcomes (laparoscopy versus open surgery: for DFS, aHR=1.16, 95% CI=0.63-2.12, P=0.636; for OS, aHR=1.11, 95% CI=0.52-2.38, P=0.794) (24). Comparing DFS between minimally invasive surgery and laparotomic surgery in patients with high-risk EC, the study conducted by Segarra-Vidal et al included 626 patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…So far, some retrospectively designed studies about the oncological safety of minimally invasive surgery for type II EC have been published. Including 295 patients from four Chinese teaching hospitals, the study conducted by Xu et al found that for apparent early-stage uterine serous carcinoma, the approach of surgical staging was not an independent prognostic factor for oncological outcomes (laparoscopy versus open surgery: for DFS, aHR=1.16, 95% CI=0.63-2.12, P=0.636; for OS, aHR=1.11, 95% CI=0.52-2.38, P=0.794) (24). Comparing DFS between minimally invasive surgery and laparotomic surgery in patients with high-risk EC, the study conducted by Segarra-Vidal et al included 626 patients (25).…”
Section: Discussionmentioning
confidence: 99%